Leg Length Discrepancy Effects on Range of Motion in Lower Limb During Walking - Azizan, N. A.; Salhani, D. A.; Basaruddin, K. S.; Salleh, A. F.; Rusli, W. M. R.; Sulaiman, A. R. (International Journal of Engineering and Technology, 2018)
Leg length discrepancy (LLD) refers to the medical condition where both legs are noticeable unequal length that could affect the gait and posture, thus may lead to various orthopedic disorders that can have serious repercussions on the individual. In order to ameliorate the rehabilitation of individuals with LLD, it is important to understand the biomechanics of LLD in these individuals. This paper presents a study to investigate on the effect of LLD on the hip and knee joint range of motion. Sandal with insoles was used to simulate the artificial LLD. The sandal’s thickness was increased starting from 0.5 cm up to 4.0 cm with 0.5 cm increment. Eighteen healthy subject need to walk over two force plates. Visual 3D and Qualisys Track Manager (QTM) system were employed for data processing. ROM was compared using the one-way blocked analysis of variance and paired t-test. The results showed that a statistically significance difference in hip and knee ROM for long leg in frontal and sagittal direction, respectively. The ROM for hip was found significance at the minimum LLD level of 2.5 cm while for knee at 1.0 cm. No significance difference found in hip and knee ROM for short leg.